Developing education materials for caregivers of culturally and linguistically diverse patients: Insights from a qualitative analysis of caregivers' needs, access and understanding of information. (14th February 2019) - Schaffler, Jamie L.; Tremblay, Sarah; Laizner, Andréa M.; Lambert, Sylvie
Abstract: Objectives: To explore the information needs of caregivers of culturally and linguistically diverse (CALD) patients, and how they access and understand health information related to the management of their care person's chronic illness(es). Background: Caregivers of CALD patients experience greater unmet needs compared to the general caregiver population. They experience many challenges in identifying resources and accessing formal supports to aid in self‐management behaviours. Methods: Eleven caregivers were recruited from outpatient clinics in Québec, Canada. Consenting caregivers participated in one face‐to‐face or phone interview. A qualitative descriptive design and inductive content analysis were used to identify themes. Results: Caregivers described a "village" approach to caregiving in which more than one individual was involved in patient care. The specific roles ascribed to caregivers defined their information needs. Caregivers described two categories of information needs: perceived and unperceived. Perceived information needs were explicit, and centred on the medical management of illnesses. Unperceived needs were unrecognized knowledge gaps that emerged during interviews and focused on self‐care. Conclusion: Although caregivers' perceived needs are often met, their unperceived needs remain unmet. Health‐care providers should perform need assessments to identify caregivers' unperceived needs, with the aims of providing culturally competent care and ongoing support.